Cultural Characteristics and Fruiting Body Production in Cordyceps bassiana - Lee, Je-O (The Korean Society of Mycology, 2010)
Single ascospore isolates of Cordyceps bassiana were observed for their colony pigmentation on Sabouraud Dextrose agar plus Yeast Extract (SDAY) plates and were inoculated in a brown rice medium for production of fruiting bodies. Colony pigmentation did not show any relationship with perithecial stromata formation. The isolates were also grown on opposite sides of SDAY agar plates and were observed for vegetative compatibility. Neither vegetative compatibility nor perithecial stromata could be found to be related to each other. It was concluded that fertile fruiting body production was independent of colony pigmentation and vegetative compatibility. Synnemata formation was found to be more common than perithecial stromata formation. This might be due to its highly conidiogenous anamorphic stage, i.e., Beauveria bassiana.